Monumentale Beeldhouwkunst. (Wetteren : Geo Art vzw, 1990)
Bracke, Jo ; Bockstaele, Herman ; Brehmer, Andreas ; Calmeyn, Jan ; Camps, Leo ; Cottenier, Joost ; Claessens, Dominik ; De Buck, Noel ; Decq, Bart ; De Maeyer, Jacky ; Demangel, Chris ; Desmet, Etienne ; De Pelsmaeker, Lieve ; Devrieze, Jeffrie ; Germonpre, Gerrit ; Mouton, Jef ; Monteyne, Roland ; Pecqueux, Gino Gildo ; Perneel, Paul ; Van Broeck, Leonard ; Van Cauwenberghe, Noel Annie ; Van den Brande, Frans ; Van Geert, Anne ; Van Gysegem, Paul ; Van Rafelghem, Paul ; Van der Vekens, Hugo ; Vastesaeger, Ludo ; Vercaemer, Geert ; Verbruggen, Mark
Monumentale Beeldhouwkunst, RMS Berlare, 27.04 - 13.05.1990 / KTA II Dendermonde, 18.05 - 10.06.1990 / RMS De Haan, 23.06 - 19.08.1990 / RIBSO Aalst, 31.08 - 15.10.1990 / RBS Zwijndrecht, 27.10 - 30.11.1990
boek